2018
DOI: 10.1051/matecconf/201820306010
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Steel-Concrete Composite Beam using Bolted Shear Connectors: A Review

Abstract: Conventional steel-concrete composite beams have been recognized to exhibit stronger structural characteristics, in terms of strength and stiffness, when compared to pure steel or reinforced concrete beams. However, currently most steel beam is fully attached to the concrete slab; this means that the shear connectors are welded through the steel decking on to the steel beam and cast into concrete slab to fulfill the necessary shear connection. Recently, the deconstruction and reuse of the components almost imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Problematikou u použití šroubových spojů je i počáteční prokluz způsobený vůli vyvrtaného otvoru pro šroub, který sice neovlivní celkovou únosnost, ale může mít vliv na chování při provozním zatížení. Studii porovnávající slepé šrouby bez matky nebo s jednoduchou či dvojitou zapuštěnou matkou provedl pomocí modelování tým z univerzity Putra v Malajsii [5]. Experimentálně výzkum s různými typy slepých šroubů a jejich porovnání s přivařenými šrouby provedl tým z univerzity ve Vietnamu [6].…”
Section: Popis Současného Stavuunclassified
“…Problematikou u použití šroubových spojů je i počáteční prokluz způsobený vůli vyvrtaného otvoru pro šroub, který sice neovlivní celkovou únosnost, ale může mít vliv na chování při provozním zatížení. Studii porovnávající slepé šrouby bez matky nebo s jednoduchou či dvojitou zapuštěnou matkou provedl pomocí modelování tým z univerzity Putra v Malajsii [5]. Experimentálně výzkum s různými typy slepých šroubů a jejich porovnání s přivařenými šrouby provedl tým z univerzity ve Vietnamu [6].…”
Section: Popis Současného Stavuunclassified
“…Qian Wang [57] demonstrated that the shear resistance and shear stiffness of largediameter, high-strength studs are greater than those of conventional stud connectors. Nadiah Loqman [58], The purpose of this paper is to examine the applicability and efficiency of composite beams with precast concrete slabs and bolted shear connectors by analysing the structural behaviour of composite beam systems, such as their strength, stiffness, slip behaviour, failure mode, and sustainability, as determined by experiment and numerical studies. K.Sathish Kumar [59], the general behaviour of composite beams with shear connectors under bending, the influence of a variety of significant characteristics was investigated.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Steel-concrete composite beams are usually composed of steel beams, reinforced concrete slabs, and shear connectors, which generally exhibit excellent structural performance in terms of strength and stiffness [1]. Structural Fire safety is an important research topic [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, extensive research studies on the fire resistance of conventional composite beams have been conducted, including experiments, and numerical and theoretical analyses [6][7][8][9][10]. Shear connectors between the concrete slab and the steel beam are usually used to transfer the longitudinal shear forces at the concrete-steel interface [11]. In conventional composite beams, the shear connectors are mostly welded on the upper flange of steel beams (such as stud, channel steel, etc.)…”
Section: Introductionmentioning
confidence: 99%